'Je suis une étrangère de partout': the material realities of exile in Tony Gatlif's Exils (2004). Issue 1 (2nd January 2017) - Davies Hayon, Kaya
Abstract: Since the new millennium, films featuring Maghrebi(-French) characters have begun to address a broad range of topographies and a number of road movies have emerged that show their protagonists making journeys between France and the countries of the Maghreb. One such film is Exils, a transnational road movie that follows Zano (Romain Duris), the French son of pieds - noirs, and Naïma (Lubna Azabal), a young Algerian-French woman, on a spontaneous journey of (self-)discovery that begins in Paris and concludes in Algeria. Drawing upon Merleau-Ponty's corporeal phenomenology and Sobchack's work, this article argues that Exils uses its protagonists' 'return' journeys to examine the lived and embodied experience of exile, as well as the politics of being displaced to a new space and time. It focuses on the two characters' differing responses to their 'homeland' and argues that Zano is able to (re)connect with his roots through his body. Naïma, on the other hand, remains in a perpetual state of alienation until the penultimate sequence of the film, in which her engagement in a Sufi trance ritual enables her to feel embodied, emplaced and (re)connected with her country and culture of origin. Throughout the course of the narrative, Exils uses its central characters' lived and embodied encounters with the people and culture of their country of origin to explore the material realities of exile and to mediate intercultural relations between France and Algeria.